Lucas Guevara - Díaz Guerra, Alirio, 1862- (Recovering the U.S. Hispanic Literary Heritage Project publication., 2003)
"From Lucas Guevara on, the Hispanic novel of immigration developed as a counter-narrative to the myths of the American Dream and the melting pot. Especially noteworthy are Diaz Guerra's satirical descriptions of the nightlife in the Bowery and the culture of New York boarding houses during the period when at least forty percent of the city's inhabitants were immigrants. Kanellos and Hernandez trace the author's development as a writer and study Lucas Guevara in the context of Hispanic history and immigrant literature."--Jacket.